2013
DOI: 10.3892/or.2013.2295
|View full text |Cite|
|
Sign up to set email alerts
|

RNA interference-mediated FANCF silencing sensitizes OVCAR3 ovarian cancer cells to adriamycin through increased adriamycin-induced apoptosis dependent on JNK activation

Abstract: In the present study, we downregulated FANCF expression by small interfering RNA (siRNA) in OVCAR ovarian cancer cells to address the effects of decreased FANCF expression on the function of the Fanconi anemia (FA)/breast cancer susceptibility gene (BRCA) pathway. Furthermore, we investigated whether this method increases the sensitivity of OVCAR3 cells to adriamycin (ADM) and the possible mechanism(s). We found that silencing of FANCF inactivated the FA/BRCA pathway by decreasing the monoubiquitination and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Reversing cancer cell resistance to apoptosis may be an effective way to suppress cancer malignancies (27). Our previous studies demonstrated that FANCF inhibition induced apoptosis of cancer cells such as ovarian (28) and breast cancer cells (17). In this study, we found that FANCF silencing potentiated the sensitivity of MMC, the combination treatment inhibited cell proliferation, increased apoptosis compared with MMC treatment alone ( Figs.…”
Section: Discussionsupporting
confidence: 51%
“…Reversing cancer cell resistance to apoptosis may be an effective way to suppress cancer malignancies (27). Our previous studies demonstrated that FANCF inhibition induced apoptosis of cancer cells such as ovarian (28) and breast cancer cells (17). In this study, we found that FANCF silencing potentiated the sensitivity of MMC, the combination treatment inhibited cell proliferation, increased apoptosis compared with MMC treatment alone ( Figs.…”
Section: Discussionsupporting
confidence: 51%
“…The possible explanation is hypermethylation at FANCF promoter region can result in FANCF gene silencing which decreases the monoubiquitination of FANCD2, giving rise to the inactivation of FA/BRCA pathway and bringing about partial or complete failure of DNA repair, followed by the induction of transforming the normal cells to cancer cells. 21 D’Andrea found that FA/BRCA pathway was a susceptibility pathway for breast cancer and Wang et al suggested that through disrupting the FA/BRCA pathway, promoter hypermethylation of FANCF plays an important role in the occurrence of ovarian cancer. 7,22 In accordance with this result and in consistence with the previous studies, we conclude that hypermethylation at the promoter of FANCF may be a potent predicator for the occurrence of EOC.…”
Section: Discussionmentioning
confidence: 99%
“…Total and nuclear proteins extraction and western blot analysis. Cells were harvested and total proteins were extracted was carried out as previously described (31), and nuclear proteins were extracted according to the manufacturer's protocol from nuclear protein extraction kit (Pierce Biotechnology, Rockford, IL, uSA). Proteins were resolved by SDS-PAGE, and transferred onto polyvinylidene fluoride membranes by electroblotting.…”
Section: Methodsmentioning
confidence: 99%